A study on hydrogen charging effects on metals for future clean energy - Chia, Jin Siang (Nanyang Technological University, 2024)
With the escalating imposition of global carbon taxes, the search for an alternative eco friendly and low-carbon energy source has started gaining traction and huge significance. Hydrogen is one of the alternatives that will emerge as we aim to become a low-carbon energy resource in the future [1]. However, introducing hydrogen into metal structures raises concerns about weakening the metals through hydrogen-induced embrittlement. Therefore, this study will employ hydrogen charging to understand how metals cope with hydrogen exposure. Hydrogen charging is a safe method that infuses metals with hydrogen for impact assessment.